Walker. Season one [videorecording (DVD)] - Yu, Jessica; Robin, Steve; Padalecki, Jared, 1982-; Morgan, Lindsey, 1990-; Hagan, Molly, 1961- (Paramount, 2021)
Follows widowed Texas Ranger Cordell Walker as he reconnects with his teenage children and fights crime with his new partner, Micki Ramirez.